Creative Economic Development Mode Through Business Learning Group For The Purpose of Ending The Poverty - Soewito SOEWITO; Suwandi SUWANDI (UBL, 2013)
Economic development is not merely about increasing the number of gaining, but also about wealth distribution. In some cases, the correlation between economic growth and wealth distribution signifies bad correlation, because the national income is only enjoyed by some certain people so it creates distance between the rich and the poor people. The high growth of economic also affects to the high budget in education because in making a better life, everything starts from improving people education. Owing to this fact, it is important to do every effort in distributing peopleâs wealth evenly. One of the indicators of a successful development is even distribution in people wealth. Based on that thing, Indonesian government nowadays has applied creative economic strategy in its effort to build its peopleâs prosperity. It is mentioned in Presidentâs instruction no. 6 2009 about the development of creative economic.The government needs to make this policy owing to the number of poor people in Indonesia which is still big either in cities or in villages. Government and societyâs role is needed in the effort to stimulate the people by using productive activity, such as business learning group, so that it can rise people life standard, which eventually people will be confident and independent.